NILAI PENDIDIKAN AKHLAK DALAM SYAIR IMAM AL-SYAFI’I (KAJIAN STRUKTURAL GENETIK) - Fahmi, Ari Khairurrijal; Nuruddin, Nuruddin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
The objective of this study is to investigate the moral educational values in Imam al-Syafii poem, which are consisted of nineteen verses. The method used is qualitative descriptive using structural approach. The result showed that in Imam al-syafii poem there are values of patience, honesty, sincerity, modesty of speaking, softness and moral of the nation. DOI: 10.15408/a.v1i2.1138